Extending the Sustainability-Quality Model for supporting the design of Persuasive Software Systems - Quispe-Cruz, Marcela; Condori-Fernandez, Nelly (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2022)
This research aims at providing a guiding support for the selection of relevant features and quality requirements for designing persuasive software systems. To do this, a mapping between the Persuasive System Design (PSD) model and a generic Sustainability-Quality (SQ) model was carried out. As a result of this mapping, we extended the SQ model, by adding certain types of relationships with specific features of the PSD model. A Graph database tool, named Neo4j, was used for facilitating the visualization of the identified relationships. And we also used the query language Cypher in order to retrieve data from the graph. Finally, we used an existing persuasive software system for illustrating the usefulness of the extended SQ model represented as graphs.